Occurrence of candicine (p-HYDROXYPHENYLETHYLTRIMETHYLAMMONIUM) in extracts of the skin of leptodactylus pentadactylus pentadactylus - Erspamer, V. (1963)
CANDICINE has been known for more than 30 years to be a natural constituent of some plants, more precisely of some Argentinian Cactaceae. The compound has now been found to occur in a vertebrate tissue also. The dry skin of five specimens of Leptodactylus pentadactylus pentadactylus, an Amazonium amphibian, was extracted twice with 70 per cent acetone. The combined extracts were concentrated under reduced pressure and the aqueous liquid shaken repeatedly with petroleum ether to remove fats. Then evaporation was continued and the syrupy residue taken up, by stirring, in 100 ml of 99 per cent ethanol. The liquid was then passed through a column of alkaline alumina. Elution was carried out with decreasing concentrations of ethanol, as described in detail in other papers. ’ The different eluates were suitably concentrated and then chromatographed on Whatman no. 1 paper.